The worst-case scenario survival handbook : weird junior edition - Borgenicht, David; Gonzales, Chuck; Heimberg, Justin (San Francisco, Calif. : Chronicle Books, 2010)
Combines history, science, and humor in a look at how to survive a Mars landing, get ready for time travel, fight a werewolf, and perform other unlikely tasks.
Aliens and other outer-space oddities -- Monsters, mummies, and more -- Hauntings and other mysteries -- Time travel -- Magic and myth.
Kirkus Review
School Library Journal
Kirkus Review, April 2010
School Library Journal, November 2010
6.8
3-6
Keywords: Curiosities and wonders -- Juvenile literature; Survival -- Juvenile literature; Curiosities and wonders; Survival; Curiosities and wonders; Survival skills